Study on antifungal effect of oligochitosan fractions prepared by irradiation combined with chemical treatment on Colletotrichum capsici causing anthracnose in Capsicum - Dũng, Phạm Đình; Thắng, Nguyễn Tiến; Xô, Dương Hoa; Luân, Lê Quang (Vietnam Journal of Biotechnology, 2018)
Chitosan was degraded by gamma rays irradiation method using 5% chitosan solution in 0.5% acetic acid with and without addition of 1% H2O2 for preparation of oligochitosan. The oligochitosan product with molecular weight (Mw) 14.84 kDa prepared by radiation in combination with H2O2 treatment was used to fractionate into 5 different Mw fractions (F1: Mw < 1kDa, F2: Mw 1-3 kDa, F3: Mw 3-10 kDa, F4: Mw 10-30 kDa và F5: Mw > 30 kDa) for testing its biological effects on red pepper plant (Capsicum frutescens L.). The obtained results showed that all separated fractions had the growth promotion effects on the increase of fresh biomass (9.9 - 56.3%) and chlorophyll content (20 - 92%) compared to those of the control one. In addition, the in vitro test of antifungal effect of separated fraction against C. capsici causing anthracnose on capsicum indicated that the fractions F3, F4 and F5 with Mw ≥ 3 kDa inhibited the growth of C. capsici colonies in a Potato Dextrose Agar (PDA) media at the concentration of 0.5%. While the the results from in vivo tests pointed out that the fractions F2, and F3 with the Mw in range of 1-10 kDa not only strongly stimulated the defense respose of tested plants to this pathogenic fungi causing anthracnose desease, but also the increased significantly gains of fruit biomass in 39 - 47%. Thus the oligochitosan fractions with Mw 1-10 kDa are quite good products for both growth promotion efect as well as antifungal purpose for C. capsici causing anthracnose desease on capsicum.